3D Auxetic Metamaterials with Elastically‐Stable Continuous Phase Transition. Issue 34 (18th October 2022) - Wang, Lianchao; Ulliac, Gwenn; Wang, Bing; Iglesias Martínez, Julio A.; Dudek, Krzysztof K.; Laude, Vincent; Kadic, Muamer
Abstract: In solid state physics, phase transitions can influence material functionality and alter their properties. In mechanical metamaterials, structural‐phase transitions can be achieved through instability or buckling of certain structural elements. However, these fast transitions in one mechanical parameter typically affect significantly the remaining parameters, hence, limiting their applications. Here, this limitation is addressed by designing a novel 3D mechanical metamaterial that is capable of undergoing a phase transition from positive to negative Poisson's ratio under compression, without significant degradation of Young's modulus (i.e. the phase transition is elastically‐stable). The metamaterial is fabricated by two‐photon lithography at the micro‐scale and its mechanical behavior is assessed experimentally. For another choice of structural parameters, it is then shown that the auxetic behavior of the considered 3D metamaterial class can be maintained over a wide range of applied compressive strain. Abstract : In this work, a novel 3D mechanical metamaterial that is capable of undergoing a phase transition from positive to negative Poisson's ratio under compression is designed, without significant degradation of Young's modulus (i.e. the phase transition is elastically‐stable). Moreover, the auxetic behavior of the considered 3D metamaterial can be maintained over a wide range of applied compressive strain.